Effectiveness of Using Economic Analysis in Managing Digital Marketing Campaigns: A Study in the Service Industry - Aryani Sairun; Sugito (Outline Journal of Economic Studies, 2025)
This study aims to analyze the effectiveness of using economic analysis in managing digital marketing campaigns in the service industry. A quantitative approach was used with a descriptive-verification design, and data were collected through questionnaires and documentation from 45 service companies in Medan. The main variables studied included Return on Marketing Investment (ROMI), Customer Lifetime Value (CLV), and customer acquisition costs. The results of multiple linear regression analysis showed that all three variables significantly influenced the effectiveness of digital campaigns. ROMI had the most dominant influence (estimate = 0.482), followed by CLV (estimate = 0.365), while acquisition costs showed a negative influence (estimate = -0.213). The coefficient of determination (R²) value of 0.617 indicates that more than 60% of the variation in campaign effectiveness can be explained by this model. This study proves that integrating economic analysis into digital marketing strategies can improve budget efficiency, segmentation accuracy, and promotional success. These findings provide strategic implications for service industry players to utilize analytical data and economic metrics in designing digital campaigns that are sustainable, measurable, and oriented towards long-term customer value.